2011
DOI: 10.1002/dvdy.22767
|View full text |Cite
|
Sign up to set email alerts
|

A focal adhesion protein‐based mechanochemical checkpoint regulates cleft progression during branching morphogenesis

Abstract: Cleft formation is the initial step of branching morphogenesis in many organs. We previously demonstrated that ROCK 1 regulates a non-muscle myosin II-dependent mechanochemical checkpoint to transition initiated clefts to progressing clefts in developing submandibular salivary glands. Here, we report that ROCK-mediated integrin activation and subsequent formation of focal adhesion complexes comprise this mechanochemical checkpoint. Inhibition of ROCK1 and non-muscle myosin II activity decreased integrin β1 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the spatial progression of a cleft deeper into the epithelium mirrors the increase in cell-ECM adhesions formed by the epithelial cells, which preferentially lose membrane localization of E-cadherin in these regions, denoting a reduction in cell-cell adhesion (Sakai et al, 2003). The presence of fibronectin in the stabilized cleft stimulates integrin-mediated signaling and proliferation of the adjacent epithelial cells, which helps to deepen the cleft (Daley et al, 2009(Daley et al, , 2011. Fibronectin also induces the expression of Btbd7 in the adjacent epithelial cells, which in turn represses E-cadherin and activates Slug (Onodera et al, 2010).…”
Section: Matrix-driven Branchingmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the spatial progression of a cleft deeper into the epithelium mirrors the increase in cell-ECM adhesions formed by the epithelial cells, which preferentially lose membrane localization of E-cadherin in these regions, denoting a reduction in cell-cell adhesion (Sakai et al, 2003). The presence of fibronectin in the stabilized cleft stimulates integrin-mediated signaling and proliferation of the adjacent epithelial cells, which helps to deepen the cleft (Daley et al, 2009(Daley et al, , 2011. Fibronectin also induces the expression of Btbd7 in the adjacent epithelial cells, which in turn represses E-cadherin and activates Slug (Onodera et al, 2010).…”
Section: Matrix-driven Branchingmentioning
confidence: 99%
“…More recently, time-lapse imaging analysis of salivary branching has shown that each cleft first initiates as a gap between adjacent epithelial cells (Kadoya and Yamashina, 2010;Larsen et al, 2006), in a process that appears to depend on ERK1/2 signaling (Koyama et al, 2008) downstream of EGF from the surrounding mesenchyme (Kashimata et al, 2000;Nogawa and Takahashi, 1991). Once clefts have initiated on the surface of the epithelium, they appear to be stabilized when the epithelial cells lining the clefts form cell-ECM adhesions that contain activated focal adhesion kinase (FAK) (Daley et al, 2011). Here, FAK appears to be acting as a mechanosensor, and is required for the subsequent assembly of ECM fibrils within the growing cleft.…”
Section: Matrix-driven Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryonic mouse submandibular salivary glands (SMGs) were dissected from timed-pregnant female mice (strain CD-1, Charles River Laboratories, Wilmington, MA) at embryonic day 12.5 or 13 (E12.5 or E13, with the day of plug discovery designated as E0), following protocols approved by the University at Albany IACUC committee. Embryonic tissues were microdissected as previously described 46,47 and cultured at the air/media interface on Nuclepore Track-Etch polycarbonate membrane filters (0.2 mm pore size, Whatman) floating on 1:1 DMEM/Ham's F12 medium (F12) (Invitrogen) supplemented with 150 mg/ml Vitamin C, 50 mg/ml Transferrin and 1X pen/strep. Five or more intact SMGs or epithelial rudiments were tested in each condition with experiments repeated at least 3 times.…”
Section: Experimental Procedures Ex Vivo Organ Culturementioning
confidence: 99%
“…At 8, 12, 18, or 22 weeks of age, mice were euthanized following the University at Albany IACUC‐approved procedures, as previously described (Daley et al, ), and submandibular salivary glands were removed from each mouse. We collected tissues from a total of six mice per time point for each mouse strain.…”
Section: Methodsmentioning
confidence: 99%